The importance of coping strategy in improving thinking and spirituality - Sharafutdinova, Khadichahon; Almardonova, Salomat (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article discusses the concepts of copping strategy, thinking, spirituality and the importance of copping strategy in enhancingthe thinking and spirituality of the individual